Factors Playing a Role in the Formation of Food Concepts in Early Childhood - Maghfira, Mutiara Aisha; Pudjiati, Sri Redatin Retno (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Early childhood is a crucial period of life to promote children’s healthy eating habits. Since food concept is an important predictor of successful interventions of eating behavior, more knowledge is needed about food concept in early childhood. Food concept is a scheme that underlies eating behavior. Moreover, it is influenced by the culture and formed by eating habits and children’s significant others. Meanwhile, there is little known about food concept among preschool children in Indonesia, whereas food concept in Indonesia can be used as a guide to diminish the numbers of eating problems. This study used qualitative research using dyadic interviews to describe food concept on preschool children (4─6 years old) and its concept formation. The interview guide used in this study is adapted and has adjusted with Indonesian culture Slaughter & Ting (2010). Four participants indicated characteristics of preoperational thought when explained food concept, covered purpose of eating, effects of different quantities of food, types, and features of healthy and unhealthy food. Each parent and caregiver described social experience that play a role in the formation of children’s food concept, which is parents (mother and father), another family members (e.g grandmother and grandfather), housemaid, school, and media. The results of this study also show that the formation of food concepts is obtained through eating habits, ways of eating, preferred types of food, feeding rules and strategies, food introduction and responses to new foods.Masa kanak-kanak awal merupakan periode penting untuk membiasakan perilaku makan agar tidak mengalami kesulitan makan. Konsep makanan yang dimiliki anak merupakan skema yang mendasari perilaku makan dan mempengaruhi keberhasilan intervensi perilaku makan pada anak. Penelitian ini menggunakan pendekatan kualitatif dengan wawancara berpasangan (anak dan orang tua) untuk melihat gambaran konsep makanan pada anak usia prasekolah (4─6 tahun) serta pembentukan konsep makanan tersebut. Empat orang partisipan menunjukkan pemahaman bahwa tujuan dari makan bahwa makan berguna bagi tubuh. Anak usia prasekolah telah mengetahui tentang makanan sehat dan tidak sehat dari bentuk, rasa, serta dampaknya bagi kesehatan tubuh. Wawancara dengan orang tua dan pengasuh dari masing-masing partisipan menggambarkan faktor pengalaman sosial yang berperan dalam pembentukan konsep makanan, terdiri dari orang tua (ibu dan ayah), anggota keluarga lain (nenek dan kakek), pengasuh/asisten rumah tangga, sekolah, dan media. Hasil penelitian ini juga menunjukkan bahwa pembentukan konsep makanan anak usia prasekolah diperoleh melalui kebiasaan makan, cara makan, jenis makanan yang disukai, aktivitas saat makan, aturan makan, strategi yang dilakukan, pengenalan makanan, dan respon terhadap makanan baru.